Simulation-based evaluation of power efficiency and output capacitance in standalone PV MPPT buck converters using 200 V p-GaN HEMTs - Liu, Xinzhi; Shafie, Suhaidi; Mohd Radzi, Mohd Amran; Azis, Norhafiz; Abdul Karim, Abdul Hafiz; Norddin, Nurbahirah; Lawal, Ismail (Korean Institute of Electrical Engineers, 2025)
This study addresses the inefficiencies and limitations of conventional silicon-based MOSFETs in photovoltaic (PV) Maximum Power Point Tracking (MPPT) buck converters by introducing a simulation based approach to assess 200 V Schottky p-GaN High Electron Mobility Transistors (HEMTs). Motivated by the need for more efficient and reliable renewable energy solutions, the study explores the advantages of Gallium Nitride (GaN) devices in overcoming challenges such as limited power capacity, poor efficiency, and heat dissipation inherent in traditional semiconductors. By integrating MATLAB Simulink and SPICE simulation techniques, the transfer characteristics of GaN HEMTs are compared against those of MOSFET and Silicon Carbide (SiC) devices, with a specific focus on the impact of output capacitance (COSS) extraction on system performance. A duty cycle controlled Perturb and Observe (P&O) MPPT algorithm is introduced, and a comprehensive evaluation of a standalone PV array under varying irradiance conditions is conducted. The analysis extends to a hard-switching multi-pulse test under constant input, contrasting GaN with MOSFET and SiC devices to highlight GaN’s superior efficiency and suitability for remote energy applications. Conclusive simulations reveal that 200 V p-GaN HEMTs exhibit 2.24 times lower average power losses during hard-switching cycles compared to MOSFETs, demonstrating their exceptional performance in optimizing standalone PV MPPT buck converters. This advancement significantly contributes to enhancing the efficiency and reliability of renewable energy systems globally.